Regular and chaotic solutions in BEC for tilted bichromatical optical lattice - Tosyali, Eren; Aydogmus, Fatma; Yilmaz, Ayberk (World Scientific Publ Co Pte Ltd, 2018)
We investigate a Bose-Einstein condensate held in a 1D tilted bichromatical optical lattice potential by constructing its Poincare sections in phase space. We explore dynamic of the system based on the relations between the system parameters and the solution behaviors. It is demonstrated that the system exhibits shock-wave like dynamic. The power spectrum graphs, bifurcation and Lyapunov exponents of BEC system are also presented.
Keywords: Bose-Einstein Condensate; Gross-Pitaevskii Equation; Optical Lattice Potential; Chaos; Bose-Einstein Condensation; Gas